THE IMPLEMENTATION OF PROBLEM BASED LEARNING (PBL) MODEL TO IMPROVE STUDENTS’ MATHEMATICAL CREATIVE THINKING ABILITY IN JUNIOR HIGH SCHOOL - Jenyfah Sebril Manurung; Bornok . Sinaga (INSPIRATIF : JURNAL PENDIDIKAN MATEMATIKA, 2018)
ABSTRACT The aim of this research is to improve students’ mathematical creative thinking ability in the classroom taught using Problem Based Learning (PBL). The design of this research is Classroom Action Research (CAR). The object of this research is the implementation of PBL model. Thesubject of this research is all students in class VIII-A SMP Negeri 4Balige academic year 2017/1018 consist of 32 students. The result of this research are: (1) The number of students who reach category completed for MCTA test in cycle I are 8 persons with percentage of completeness is 25%, students not completed are 24 persons with percentage of completeness is 75% and the score of MCTA reached is 1,97 in low criteria, (2) The number of students who reach category completed for MCTA test in cycle II  are 25 persons with percentage of completeness is 78,125%, students not completed are 7 persons with percentage of completeness is 21,875% and the score of MCTA reached is 2,81 in high criteria (3) Learning by implemented PBL model could make the students’ activity was good category in learning, and (4) Learning by implemented PBL model can improve students’ mathematical creative thinking ability.Keywords: Mathematical Creative Thinking,  Problem Based Learning